Comunicazioni dell'Istituto Papirologico «G. Vitelli» 14 - Russo, Simona (Edizioni dell'Istituto Papirologico «G. Vitelli», 2022)
Volume 14 of the Comunicazioni dell'Istituto Papirologico «G. Vitelli» is divided into three sections: 1. Editions and rieditions of texts; 2. Critical notes; 3. Chronique de lexicographie papyrologique de la vie matérielle. The first section includes the editio princeps of a papyrus of the Cambridge collection, and the new edition of two texts kept in Leipzig and Vienna. The second section includes a paper on a fragment of Archilochos, and another one on the festal letters. The third section, as in the previous volumes, concerns the international research project Contextes et mobiliers, de l'époque hellénistique à l'époque mamelouke. Approches archéologiques, historiques et anthropologiques (led by IFAO) and is divided into three sections: bibliographic update (Bulletin); corrections and notes on already published texts (Corr.Lex.Mat.); specific contributions on the lexicography of material culture (Études).